Electrolyte for rapidly charging lithium metal battery
By using organic carbonate solution and electrolyte of 3-cyclobutylsulfone and LiNO3 in lithium metal batteries, a high ion conductivity SEI film was constructed, which solved the problems of lithium dendrites growth and battery performance deterioration, and realized lithium metal batteries High cycle stability and long life under fast charging conditions.
Patent Information
- Application Number
- CN202411381660.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium metal batteries are prone to growth of lithium dendrites under fast charging conditions, resulting in deterioration of battery performance and safety hazards. It is mainly due to the instability and irreversible decomposition of the electrode/electrolyte interface. The existing electrolyte optimization solutions are complex and difficult to achieve large-scale production.
Using an electrolyte containing an organic carbonate solution, a lithium salt and a mixture of 3-cyclobutylsulfone and LiNO3, lithium is inhibited by constructing a solid electrolyte interface (SEI) film with high ionic conductivity and high mechanical strength on the surface of lithium metal. Dentite growth and enhances the uniformity of lithium deposition.
The cycle life and capacity retention rate of lithium metal batteries is significantly improved under high current density and high magnification conditions, with stable cycles of more than 100 times, and exhibits excellent cycle stability and high electrochemical reversibility among different battery types.
Smart Images

Figure CN119253071A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrolytes, and in particular relates to an electrolyte for fast charging of lithium metal batteries. Background Art
[0002] With the rapid development of consumer electronics, electric vehicles, smart grids and other fields, human society's demand for high-energy-density batteries has increased significantly. Although existing lithium-ion batteries have achieved great success in commercial applications, their energy density is currently close to the theoretical limit and it is difficult to meet the demand for high-performance batteries in future applications. Thanks to the extremely high theoretical specific capacity of metallic lithium (about 3860mAh / g) and the lowest electrode potential (-3.04V, relative to the standard hydrogen electrode), lithium metal batteries are considered to be a strong candidate for the next generation of high-energy-density energy storage devices. However, lithium metal batteries face many challenges in practical applications, especially the compatibility of electrolytes and lithium metal anodes, which seriously restricts their commercialization process.
[0003] During the charge and discharge process of lithium metal batteries, lithium dendrite growth is prone to occur at the lithium metal negative electrode. As the number of cycles increases, lithium dendrites gradually accumulate and may eventually pierce the diaphragm, causing internal short circuits and triggering thermal runaway of the battery, thus posing serious safety hazards. Under fast charging conditions, the growth of lithium dendrites is more obvious, resulting in rapid deterioration of battery performance. The root cause of this problem lies in the instability of the electrode / electrolyte interface. The complex chemical reactions between lithium metal and traditional electrolytes, which not only lead to the formation of an uneven solid electrolyte interface (SEI), but also cause irreversible decomposition of the electrolyte, further exacerbating the instability of the lithium metal surface. In traditional electrolyte systems, solvents and lithium salts are prone to react on the surface of lithium metal to generate organic matter with low ionic conductivity. This SEI film not only hinders the rapid transmission of lithium ions, but also causes it to repeatedly break and rebuild during the charge and discharge process, resulting in continuous consumption of the electrolyte and ultimately leading to battery failure.
[0004] In order to cope with the challenges faced by lithium metal batteries in practical applications, many researchers are committed to regulating the solid electrolyte interface (SEI) film on the surface of lithium metal anode by optimizing the composition of the electrolyte to inhibit the growth of lithium dendrites and thus improve the cycle stability of the battery. However, most of the improved processes are too complicated to achieve large-scale production. Therefore, under fast charging conditions, it is still a huge challenge to achieve stable lithium metal batteries using simple electrolyte optimization schemes. Therefore, developing a simple electrolyte that can form a stable solid electrolyte interface (SEI) layer with high ionic conductivity on the surface of the lithium metal anode, thereby improving the uniformity of lithium deposition, has become a key strategy to solve this problem. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes an electrolyte for fast charging of lithium metal batteries, which can construct a SEI film with high ionic conductivity and high mechanical strength on the surface of lithium metal, thereby improving the uniformity of lithium deposition and increasing the cycle life of lithium metal batteries under fast charging working conditions.
[0006] In order to achieve the above object, the present invention is achieved through the following technical solutions:
[0007] An electrolyte for rapid charging of a lithium metal battery comprises an organic solvent, a lithium salt and an additive, wherein the organic solvent is an organic carbonate solution, the concentration of the lithium salt in the electrolyte ranges from 0.5 to 1.5 mol / L, and the additive is a mixture of 3-cyclobutene sulfone and LiNO3, and the concentrations of 3-cyclobutene sulfone and LiNO3 in the electrolyte are 0.3 to 3 mol / L and 0.05 to 0.5 mol / L, respectively.
[0008] Preferably, the organic solvent is a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC) and fluoroethylene carbonate (FEC), and the volume proportions thereof are 47.5%, 47.5% and 5%, respectively.
[0009] Preferably, the lithium salt is one or more of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium tetrafluoroborate and lithium difluorophosphate.
[0010] The beneficial effects of the present invention are:
[0011] The present invention introduces 3-cyclobutene sulfone and LiNO3 additives into carbonate electrolytes. 3-cyclobutene sulfone can promote the dissolution of LiNO3 in commercial carbonate electrolytes. Li NO3 and 3-cyclobutene sulfone can preferentially undergo reduction reaction on the surface of lithium metal, and generate inorganic nitrides, sulfides and oxides through reduction decomposition, thereby constructing a SEI film with high ionic conductivity and high mechanical strength on the surface of lithium metal, thereby improving the uniformity of lithium deposition and increasing the cycle life of lithium metal batteries under fast charging working conditions. In a lithium||copper (Li||Cu) half-cell, at 2mA / cm 2 High current density and 2mAh / cm 2 At the surface capacity of 100, it can stably cycle 100 times; in the lithium||lithium (Li||Li) symmetric battery, at 3mA / cm 2 High current density and 3mAh / cm 2At the surface capacity of 1000mA / g, it can stably cycle for 300h; in the lithium||lithium iron phosphate (Li||LiFePO4) full battery, after 1000 and 4000 cycles at high rates of 5C and 20C (1C=170mA / g), it can still show a capacity retention rate of more than 90%. Its long cycle performance has been greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0013] Figure 1 The Li||Cu half-cells in Comparative Example 1 and Example 1 are at 2 mA / cm 2 The current density is 2 mA h / cm 2 Cyclic performance diagram under surface capacity.
[0014] Figure 2 The Li||Li symmetric battery in Comparative Example 2 and Example 2 is 3 mA / cm 2 The current density is 3 mA h / cm 2 Cyclic performance diagram under surface capacity.
[0015] Figure 3 This is the SEM morphology of lithium metal after the Li||Li symmetric battery cycle in Comparative Example 2.
[0016] Figure 4 This is a SEM morphology of lithium metal after the Li||Li symmetric battery in Example 2 was cycled.
[0017] Figure 5 It is a cycle performance diagram of the Li||LiFePO4 full battery in Example 3 and Example 3 at a 5C rate and a charge and discharge window of 2.5 to 4.0V.
[0018] Figure 6 It is a cycle performance diagram of the lithium metal battery in comparative example 4 and embodiment 4 at a rate of 20C and a charge and discharge window of 2.5 to 4.0V. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0020] If no specific experimental steps or conditions are specified in the examples and comparative examples, the conventional experimental steps or conditions described in the literature in the art can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.
[0021] Embodiment 1:
[0022] First, prepare the experimental group electrolyte: In an inert gas atmosphere, mix 167 mg of LiPF6, 7 mg of LiNO3, 60 mg of 3-cyclobutene sulfone, 0.5 mL of EC, 0.5 mL of DMC and 0.5 mL of FEC and stir for 12 hours to obtain the experimental group electrolyte. Then, use the above electrolyte and lithium sheet, copper sheet and polypropylene microporous membrane to assemble Li||Cu half-cell. The prepared battery has a current of 2 mA / cm 2 The current density is 2 mAh / cm 2 The cycle performance test was carried out under the surface capacity.
[0023] Comparative Example 1
[0024] First, prepare the control group electrolyte: In an inert gas atmosphere, mix and stir 167 mg of LiPF6, 0.5 mL of EC, 0.5 mL of DMC and 0.5 mL of FEC for 12 hours to obtain the control group electrolyte. Then, use the above electrolyte and lithium sheet, copper sheet and polypropylene microporous separator to assemble Li||Cu half-cell. The prepared battery is 2 mA / cm 2 The current density is 2 mAh / cm 2 The cycle performance test was carried out under the surface capacity.
[0025] Figure 1 The Li||Cu half-cells in Comparative Example 1 and Example 1 are shown in Figure 1 at a current density of 2 mA / cm 2 The dough capacity is 2mAh / cm 2 The results show that the coulombic efficiency of the Li||Cu half-cell in Comparative Example 1 drops significantly after 20 cycles, while the Li||Cu half-cell in Example 1 exhibits excellent cycle stability, with side reactions significantly suppressed, and can be stably cycled 100 times with an average coulombic efficiency of 97.6%. This shows that the SEI film formed by the synergistic effect of LiNO3 and 3-cyclobutene sulfone additives can significantly improve the electrochemical reversibility of the battery.
[0026] Embodiment 2:
[0027] First, prepare the experimental group electrolyte: In an inert gas atmosphere, mix 167 mg of LiPF6, 7 mg of LiNO3, 60 mg of 3-cyclobutene sulfone, 0.5 mL of EC, 0.5 mL of DMC and 0.5 mL of FEC and stir for 12 hours to obtain the experimental group electrolyte. Then, use the above electrolyte, lithium sheet and polypropylene microporous membrane to assemble Li||Li symmetric battery. The prepared battery is 3mA / cm 2 The current density is 3 mAh / cm 2 The cycle performance test was carried out under the surface capacity.
[0028] Comparative Example 2
[0029] First, prepare the control group electrolyte: In an inert gas atmosphere, mix and stir 167 mg of LiPF6, 0.5 mL of EC, 0.5 mL of DMC and 0.5 mL of FEC for 12 hours to obtain the control group electrolyte. Then, use the above electrolyte, lithium sheet and polypropylene microporous separator to assemble Li||Li symmetric battery. The prepared battery is 3mA / cm 2 The current density is 3 mAh / cm 2 The cycle performance test was carried out under the surface capacity.
[0030] Figure 2 It shows that the Li||Li symmetric battery in Comparative Example 2 and Example 2 has a current density of 3 mA / cm 2 The dough capacity is 3mAh / cm 2 The Li||Li symmetric battery in Comparative Example 2 short-circuited after about 85 hours of cycling, indicating that its SEI film quality was poor and could not guide the uniform deposition of lithium, resulting in the growth of lithium dendrites. In contrast, the battery in Example 2 showed excellent cycling stability and could be stably cycled for more than 300 hours, showing extremely high interface stability.
[0031] Figure 3 and Figure 4 The SEM morphologies of lithium metal after the Li||Li symmetric battery cycle in Comparative Example 2 and Example 2 are shown respectively. As can be seen from the figure, the lithium deposition in Comparative Example 2 shows obvious lithium dendrite growth and uneven deposition, and the lithium deposition layer is not dense; while in Example 2, the lithium deposition has no obvious lithium dendrite growth, and the deposition is dense and uniform.
[0032] Example 3
[0033] First, prepare the electrolyte of the experimental group: in an inert gas atmosphere, mix and stir 167 mg of LiPF6, 7 mg of LiNO3, 60 mg of 3-cyclobutene sulfone, 0.5 mL of EC, 0.5 mL of DMC and 0.5 mL of FEC for 12 hours to obtain the electrolyte of the experimental group. Mix and grind lithium iron phosphate, Super P and polyvinylidene fluoride in a mass ratio of 8:1:1, add an appropriate amount of N-methylpyrrolidone, stir evenly and apply it on aluminum foil; place the above aluminum foil in a vacuum drying oven at 80°C and dry overnight, and obtain the lithium iron phosphate positive electrode sheet after cutting and rolling. Then, use the above electrolyte and lithium sheet, lithium iron phosphate positive electrode sheet and polypropylene microporous diaphragm to assemble Li||LiFePO4 full battery. The prepared battery is tested for cycle performance under the conditions of 5C rate and charge and discharge window 2.5~4.0V.
[0034] Comparative Example 3
[0035] First, prepare the control group electrolyte: In an inert gas atmosphere, mix and stir 167 mg of LiPF6, 0.5 mL of EC, 0.5 mL of DMC and 0.5 mL of FEC for 12 hours to obtain the control group electrolyte. Mix and grind lithium iron phosphate, Super P and polyvinylidene fluoride in a mass ratio of 8:1:1, add an appropriate amount of N-methylpyrrolidone, stir evenly and apply it on aluminum foil; place the above aluminum foil in an 80°C vacuum drying oven to dry overnight, and obtain lithium iron phosphate positive electrode sheets after cutting and rolling. Then, use the above electrolyte and lithium sheet, lithium iron phosphate positive electrode sheet, and polypropylene microporous diaphragm to assemble Li||LiFePO4 full battery. The prepared battery was tested for cycle performance under the conditions of 5C rate and charge and discharge window of 2.5~4.0V.
[0036] Figure 5 The cycle performance of the lithium metal battery in Comparative Example 3 and Example 3 at 5C rate and a charge and discharge window of 2.5-4.0V is shown. The results show that the lithium metal battery in Comparative Example 3 exhibits significant capacity decay after about 400 cycles, while the battery in Example 3 still has a high discharge capacity retention rate of 94.4% after about 1000 cycles. This shows that the electrolyte additive used in Example 3 has a significant effect on the cycle stability of the lithium metal battery and significantly improves the cycle life of the battery.
[0037] Example 4
[0038] First, prepare the electrolyte of the experimental group: in an inert gas atmosphere, mix and stir 167 mg of LiPF6, 7 mg of LiNO3, 60 mg of 3-cyclobutene sulfone, 0.5 mL of EC, 0.5 mL of DMC and 0.5 mL of FEC for 12 hours to obtain the electrolyte of the experimental group. Mix and grind lithium iron phosphate, Super P and polyvinylidene fluoride in a mass ratio of 8:1:1, add an appropriate amount of N-methylpyrrolidone, stir evenly and apply it on aluminum foil; place the above aluminum foil in a vacuum drying oven at 80°C and dry overnight, and obtain the lithium iron phosphate positive electrode sheet after cutting and rolling. Then, use the above electrolyte and lithium sheet, lithium iron phosphate positive electrode sheet and polypropylene microporous diaphragm to assemble Li||LiFePO4 full battery. The prepared battery is tested for cycle performance under the conditions of 20C rate and charge and discharge window of 2.5~4.0V.
[0039] Comparative Example 4
[0040] First, prepare the control group electrolyte: In an inert gas atmosphere, mix and stir 167 mg of LiPF6, 0.5 mL of EC, 0.5 mL of DMC and 0.5 mL of FEC for 12 hours to obtain the control group electrolyte. Mix and grind lithium iron phosphate, Super P and polyvinylidene fluoride in a mass ratio of 8:1:1, add an appropriate amount of N-methylpyrrolidone, stir evenly and apply it on aluminum foil; place the above aluminum foil in an 80°C vacuum drying oven to dry overnight, and obtain lithium iron phosphate positive electrode sheets after cutting and rolling. Then, use the above electrolyte and lithium sheet, lithium iron phosphate positive electrode sheet, and polypropylene microporous diaphragm to assemble Li||LiFePO4 full battery. The prepared battery was tested for cycle performance under the conditions of 20C rate and charge and discharge window of 2.5~4.0V.
[0041] Figure 6 The cycle performance of the lithium metal battery in Comparative Example 4 and Example 4 at 20C rate and a charge and discharge window of 2.5-4.0V is shown. The results show that the capacity of the lithium metal battery in Comparative Example 4 decays very quickly, while the discharge capacity retention rate of the battery in Example 4 is still as high as 92.3% after about 4000 cycles. This shows that the electrolyte with the addition of LiNO3 and 3-cyclobutene sulfone significantly improves the cycle performance of the lithium metal battery at high rates, and its battery performance is superior to that of the electrolyte without additives.
[0042] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all details in detail, nor do they limit the invention to only the specific embodiments described. Obviously, many modifications and changes can be made according to the content of this specification.
Claims
1. An electrolyte for rapid charging of a lithium metal battery, comprising an organic solvent, a lithium salt and an additive, characterized in that: The organic solvent is an organic carbonate solution, the concentration range of the lithium salt in the electrolyte is 0.5-1.5 mol / L, the additive is a mixture of 3-cyclobutene sulfone and LiNO3, and the concentrations of 3-cyclobutene sulfone and LiNO3 in the electrolyte are 0.3-3 mol / L and 0.05-0.5 mol / L, respectively.
2. The electrolyte for rapid charging of lithium metal batteries according to claim 1, characterized in that: The organic solvent is a mixture of ethylene carbonate, dimethyl carbonate and fluoroethylene carbonate, and the volume proportions thereof are 47.5%, 47.5% and 5% respectively.
3. The electrolyte for rapid charging of lithium metal batteries according to claim 1, characterized in that: The lithium salt is one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium tetrafluoroborate and lithium difluorophosphate.
4. Use of the electrolyte according to any one of claims 1 to 3 in a fast-charging lithium metal battery.
Citation Information
Patent Citations
Lithium battery electrolyte based on sulfate additive
CN107359368A
High-voltage lithium ion battery combined electrolyte additive, electrolyte and battery thereof
CN110943253A
Formation method of lithium iron phosphate battery
CN112234270A
Lithium metal battery electrolyte and preparation method and application thereof
CN113206293A
Electrolyte for high-voltage lithium metal battery and preparation method of electrolyte
CN115395098A